KAJIAN KEBIJAKAN DAN PENGEMBANGAN SEKTOR INFORMAL KOTA PEMATANGSIANTAR - Fauzi . (Universitas Islam Sumatera Utara, 2020)
Today, the presence of the urban informal sector is considered one of the emerging economic sectors as a result of the city's high employment growth situation. Those who enter this small-scale business, initially aimed at finding job opportunities and creating income. Identify the distribution of informal sector of Pematangsiantar City, using data from plotting surveys using GPS (Global Positioning System). The distribution of business actors / informal sector activities is identified based on the number of samples taken in conjunction with the dissemination of questionnaires. The number of samples itself is determined using sampling method. The calculation itself is done by means of the number of respondents who choose one of the variables divided by the total number of respondents, namely 50 (fifty) correspondents. Weighting on internal factors of importance is based on the large influence of strategic factors on its strategic position (Freddy Rangkuti, 2001 : 22-24). The number of weights on each internal factor must amount to = 1 (one) : Total Internal Score → Total Strength Weight + Total Weight Weakness = 1. While the value of weight according to Freddy Rangkuti (2001: 22-24) and Training Spama (2000: 13-14) based on the following provisions: